온라인 인터랙티브 게임 세션들에 대한 콘텐츠를 렌더링 및 인코딩하기 위한 방법들 및 시스템들 (2022)
본 출원은 다수의 처리 슬라이스들을 더 포함하는 하나 이상의 처리 코어들을 갖는 서버 시스템의 처리 성능을 관리하는 방법에 관한 것이다. 온라인 게임 세션들을 시작하라는 요청들을 수신하면, 서버 시스템은 처리 코어들의 각각의 처리 슬라이스를 해당 슬라이스 상에서 실행될 온라인 게임 세션들의 서브세트에 할당한다. 제1 게임 세션 및 제2 게임 세션을 포함하는 온라인 게임 세션들의 제1 서브세트에 제1 처리 슬라이스가 할당된다. 제1 처리 슬라이스에서, 온라인 게임 세션들의 제1 서브세트에 대한 시간 공유 처리 스케줄이 결정된다. 시간 공유 처리 스케줄에 따라, 제1 게임 세션과 제2 게임 세션은 제1 처리 슬라이스의 듀티 사이클을 공유하고, 제1 게임 세션 및 제2 게임 세션의 실시간 데이터 처리 요구에 따라 동적으로 그리고 병렬로 실행된다. This application is directed to a method of managing processing capability of a server system having one or more processing cores that further include multiple processing slices. Upon receiving requests to initiate online gaming sessions, the server system allocates each processing slice of the processing cores to a subset of the online gaming sessions to be executed thereon. A first processing slice is allocated to a first subset of the online gaming sessions including a first gaming session and a second gaming session. At the first processing slice, a time-sharing processing schedule is determined for the first subset of the online gaming sessions. In accordance with the time-sharing processing schedule, the first and second gaming sessions share a duty cycle of the first processing slice, and are executed dynamically and in parallel according to real-time data processing need of the first and second gaming sessions.